(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2025)
The aim of this study was to ascertain the factors that influence library and information science professionals' use of social media for scholarly communication. The study adopted a quantitative technique with a questionnaire as an instrument for data collection. The study’s object of analysis was the academic staff from the selected state and federal university library schools in Northeastern Nigeria. One hundred and forty-one respondents were selected using a convenience sampling method to form the sample of the study. Descriptive analysis of frequency counts and percentage scores was used for demographic information and the frequency of scholarly communication. A structural equation modelling with SmartPLS4 was used to fulfil the research objective in a measurement model. While the four hypotheses were tested in a part coefficient through the structural model. The results indicate that library and information professionals use social media regularly for scholarly communication. It further revealed that Perceived Ease of Use, Visibility and Academic Reputation and Professional Networking Opportunities significantly influenced the use of social media for scholarly purposes with statistically significant p-values (p = 0.000, p = 0.002 and p = 0.015). These results are further reinforced by the coefficient of determination (R² = 0.720), which indicates that 72% of the variance in SCOM is collectively explained by the independent variables. Perceived usefulness, however, did not influence scholarly communication significantly. It recommended for organisations and LIS associations support for the usage of social media and the strengthening of online exposure techniques for the professionals through training, among other things.